Literature Review: Effectiveness of Family Support to Improve Quality of Life People With Mental Disorders - Rahma Tri Aristawidya; Moh. Sholeh (International Conference on Sustainable Health Promotion, 2025)
Mental disorders are currently a major problem in various parts of the world. People with mental disorders often receive negative stigma from the surrounding community regarding the mental disorders they experience. This stigma will have an impact on the quality of life of people who have mental disorders. However, in order for their quality of life to continue to improve, people with mental disorders not only need medical treatment from the hospital, but also need support from their families. This research aims to explore further the effectiveness of family support in improving the quality of life of people with mental disorders through a literature review method. This method was carried out by searching for literature from Google Schooler and ResearchGare and obtained 5 suitable journals. The results of this research show that the quality of life of people with mental disorders is influenced by the family support provided, so that family support can be said to be effective in improving the quality of life of ODGJ.